ANALISIS PENERAPAN PRINSIP-PRINSIP ISLAMIC GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Ardies Afryan; Sri Hartono (Jurnal Ekonomi dan Bisnis, 2016)
Corporate performance is ability a company to result it benefit on sale, assets and capital surest.This Research to test connection islamic corporategovernance, and corporate performance.Control Mechanicsism of islamic corporategovernance that use is shidiq, amanah, tabligh,fathanah, istiqamah dan qana’ah. This Research to use it descriptive research method withprimary data type. Sample on this research is UMKM in the Semarang. Data Analysical with touse it program SPSS 20, test classic assumption to use it test normality, test multikolinearity,and test heteroskedastisity, test hypothesical to use it analysical doubled linear regression ,determine’s coefficient, test statictic F and test Statistict. The result show that simultaneouslyshidiq, amanah, tabligh, fathanah, istiqamah and qana’ah positive influency and significant incorporate performance. According to parsial only qana’ah that influency positive and significantin corporate performance.Keywords: Islamic corporate governance, shidiq, amanah,tabligh, fathanah, istiqamah,qana’ah and corporate performance.